"Backstage moments during the campaign": The interactive use of Instagram by Spanish political leaders. (May 2022) - Pineda, Antonio; Bellido-Pérez, Elena; Barragán-Romero, Ana I
The political use of social media is a well-established field of research. We perform a content analysis of the messages posted on Instagram—one of the fastest growing social networking sites—by the leaders of the four main political parties in Spain, with special emphasis on the interactive use of this platform and the functions played by the posts. The sample of Instagram posts includes a non-election period and a period of regional elections. The results point to a practically irrelevant use of interactive tools, and an emphasis on the self-promotion of leaders and their parties. Accordingly, the data show that Instagram is basically used by Spanish leaders as a supplement to their campaign efforts and strategic objectives. These findings are discussed and linked to broader theoretical issues such as the hypothesis of normalization and the use of the Internet for broadcasting.